Influence of FRP and concrete material properties on bond slip behavior of FRP-to-concrete interface - Gan, Jin Sern (2017)
Usage of externally bonded Fibre Reinforced Polymer (FRP) as a way to strengthened RC structures has been widely used in the past decade. It has been established as an effective method for rehabilitation and recently developed as an effective way of retrofitting concrete structures for high impact events such as blasting. However, failure of debonding was commonly found in FRP retrofitted structures. The aim of this report is to investigate how the important parameters affect the bond-slip behaviour as well as bond strength of FRP-to-concrete joint. The important parameters are namely, the stiffness of FRP, FRP-to-concrete width ratio, FRP bond length, and concrete strength. An experimental setup adopting the concept of near end support single-shear test was conducted using a MTS machine under static load. The effect on bond behaviour was studied in this project. Global response of the bond behaviour such as the overall loading capacity was analysed in this report. The key elements to indicate the bond-slip behaviour and bond strength includes the peak stress and interfacial fracture energy were also evaluated. In the end of the report, a comparison between experimental bond strength and existing bond strength modal were included to give a more comprehensive assessment.